Materialism and Life Satisfaction Relations Between and Within People Over Time: Results of a Three-Wave Longitudinal Study - Jaspers E; Pandelaere M; Pieters R; Shrum LJ (Wiley)
The negative association between materialism and life satisfaction is well-documented, but it is unclear what the directionality of the association is. To address this issue, we (a) conducted a 3-wave longitudinal study (N = 6,551) over 3 years and examined the bidirectional relations between life satisfaction and materialism as a composite measure and with each of its three facets (happiness, success, centrality), and (b) estimated Random Intercept Cross-Lagged Panel Models (RI-CLPMs) that separate inter- and intra-individual effects and compared them with traditional CLPMs that do not. The traditional CLPM showed bidirectional negative associations between composite materialism and life satisfaction and strong negative bidirectional association for the happiness facet, but positive effects of the centrality facet on life satisfaction. However, and importantly, the RI-CLPM revealed that these relations exist predominantly between people. Within people, materialism does not impact life satisfaction, but life satisfaction does impact the happiness facet negatively. These findings challenge common ideas that the direction of the effect is from materialism to life satisfaction and that it is unilaterally negative.
CAUL read and publish agreement 2023
Keywords: 1505 Marketing; 1701 Psychology